Unraveling the Challenges Faced by the Kalasha: A Historical Analysis - Islam, Rabia (Al-Qanṭara, 2024)
The Durand Line Agreement was signed in 1893. It gave a new direction to the future of the Kafirs of Hindukush. The Amir was initially denied Kafiristan under this agreement, but upon his protest, the region was granted to him. He dispatched his forces swiftly and took control of the area. The neighbouring Chitral was under the influence of British. British Viceroy Lord Dufferin dispatched a mission under the command of General Lockhart to explore the population and resources of the area, but the primary goal of the British was to restrain Russian advance, not to explore the Hindukush. The invasion of Kafiristan not only transformed the political and administrative setup of the region, but the Kafir majority was reduced to a minority. Historically, the Kalasha have faced all forms of threats including slavery, taxes, conversions, terrorism, encroachments, lack of basic health facilities, and climate change. This article analyse the challenges faced by the Kalasha community in order to ensure their survival.